2019
DOI: 10.1302/2058-5241.4.180100
|View full text |Cite
|
Sign up to set email alerts
|

Os acromiale: a review of its incidence, pathophysiology, and clinical management

Abstract: An os acromiale occurs when any of the primary ossification centres of the acromion fail to fuse with the basi-acromion. It is present in approximately 8% of individuals, and whilst the majority of these individuals are unaffected it can cause significant pain and disability. It can impact seemingly unrelated surgical intervention in the region such as subacromial decompression and reverse shoulder arthroplasty. A painful os acromiale can be both a diagnostic challenge, and difficult to manage. There remain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
12
1
2
Order By: Relevance
“…Moreover, during anterior decompression, bone fragments in the spinal canal can be completely removed under direct vision [ 18 ], effectively alleviating spinal cord compression and avoiding the iatrogenic damage to the spinal cord caused by distraction during posterior decompression [ 19 ]. Anterior decompression the advantages of clear exposure during surgery, accurate decompression effect, small trauma, and fast fusion of factured vertebrae after surgery [ 20 ]. Compared with other similar research [ 7 , 11 , 15 ], the novelty of our study is that we showed anterior decompression effectually enhances the surgical outcomes, restores the physiological anatomy of fractured vertebrae, improves the postoperative nerve functions, and accelerates the recovery of urinary and sexual functions in patients with thoracolumbar spinal fractures complicated with spinal cord injury, which can improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, during anterior decompression, bone fragments in the spinal canal can be completely removed under direct vision [ 18 ], effectively alleviating spinal cord compression and avoiding the iatrogenic damage to the spinal cord caused by distraction during posterior decompression [ 19 ]. Anterior decompression the advantages of clear exposure during surgery, accurate decompression effect, small trauma, and fast fusion of factured vertebrae after surgery [ 20 ]. Compared with other similar research [ 7 , 11 , 15 ], the novelty of our study is that we showed anterior decompression effectually enhances the surgical outcomes, restores the physiological anatomy of fractured vertebrae, improves the postoperative nerve functions, and accelerates the recovery of urinary and sexual functions in patients with thoracolumbar spinal fractures complicated with spinal cord injury, which can improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of os acromionale is related to failed fusion between the mesoacromion and meta-acromion, resulting in a coronal cleft at the posterior margin of the AC joint (10,99,100). The majority of cases are asymptomatic, although some of these disorders cause pain related to an unstable synchondrosis or an impingementlike syndrome during overhead activity (101). If symptoms do not respond to conservative measures, surgical options include screw fixation of the synchondrosis or resection (13,100).…”
Section: Acromial Apophysiolysis and Os Acromionalementioning
confidence: 99%
“…It is usually detected incidentally in radiology; however, os acromiale can lead symptoms in some cases [12]. Both the diagnosis and treatment of a painful os acromiale is difficult [9].…”
Section: Introductionmentioning
confidence: 99%